Green Sukuk Sebagai Upaya Pemerintah Dalam Mewujudkan Lingkungan Hijau - Imroatus Sholiha (At-Tasharruf "Jurnal Kajian Ekonomi dan Bisnis Syariah", 2022)
AbstractGreen sukuk is an innovative Sharia-based financing that finances green projects that aim to create a green environment. Indonesia became the first country to issue green sukuk and received appreciation from other countries. The government's commitment in overcoming climate change is to make several regulations, including regulations on climate change mitigation, namely making a guide or guideline in implementing action plans in an effort to reduce greenhouse gas emissions, climate change adaptation regulations, and making strategy guidelines and action plans for biodiversity. Through Law No. 16 of 2016 concerning the work plan for the United Nations, the Indonesian government has also ratified the conversion of climate change and Indonesia is one of the countries that seriously and without coercion participates in the movement to reduce greenhouse gas emissions. Some of the projects that have been financed by the green sukuk are the construction of 491 road and bridge projects, the construction of 85 transportation sector projects, the construction of 589 water resources projects, the development of the agricultural sector, the development of 762 projects in the education sector, the construction of 21 National Defense and Security parks, construction and rehabilitation, construction and development of 19 laboratories. While the obstacles in developing green sukuk in Indonesia are the lack of human resources, lack of socialization, green sukuk may be exposed to a higher profile, as well as the many characters of each investor that make market share difficult to predict. The research approach used is descriptive qualitative, that is, in describing the research results, it does not use numbers but words. While the research method used is the library method.